Analysis of Potential Excise Imposition on High Calorie Packaged/Instant Foods: Study Case in Indonesia - Yafie Lucky Sukmana (Budapest International Research and Critics University, 2022)
Studies this aim for analyzing potency of imposition tax on high-calories packaged/instant food in Indonesia by function of excise duty policy. Study this using case study qualitative research methods by conducting in-depth interviews with potential regulators related to policy formulation and implementation as well as academics who have knowledge and expertise related topic. The results showed that high-calorie packaged/instant food was rated could fulfill regulatory nor budgetary function taxes if applied in Indonesia. A number of lessons learned in the study could be useful for the preparation and implementation process of policy tax on packaged/instant food.